ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL, PROFITABILITAS, KEBIJAKAN UTANG, DAN UKURAN PERUSAHAAN TERHADAP KEPUTUSAN INVESTASI (Studi Empiris Pada Perusahaan Manufaktur Periode 2010-2012) - B11111060, RINNY VIANY (Jurnal Manajemen Update, 2015)
This study aims to examine the influence of Managerial Ownership, Profitability,Â Leverage, and Firm Size toward Invesment Descision of the manufacturing firms listing at theIndonesia Stock Exchange period 2010-2012. The sample that used are 38 firms and they aretaken by purposive sampling. This study used the panel regression analysis with fixed effectmethod. There are one dependent variable and 4 independent variables. Dependent variableis Investment Decision (PER) and independent variables in this study are ManagerialOwnership (MOWN), Profitability (ROA), Leverage (DER), and Firm Size. The resultindicated that MOWN no significant on PER. ROA and DER have negative significant effecton PER. Firm Size have positif significant effect on PER. Four independent variables canexplain PER about of 96 %.Keywords : Invesment Decision, Managerial Ownership, Profitability, Leverage, and FirmSize